Estudio de la viabilidad de los bioplásticos a base de almidón en Colombia por medio del análisis comparativo entre dos materias primas: la papa y el maíz (2021)
Currently, the planet is affected by global warming and increasing pollution in the environment. One of the most relevant factors is the excess of plastics in the environment, these are synthetic, since they come from fossil reserves; therefore, its degradation is so complex that it causes large volumes of waste, thus generating toxic substances that contribute to an unfavorable environment for all the individuals that inhabit it.